An experimental investigation of the motion of long bubbles in high viscosity slug flow in horizontal pipes. (July 2018) - Bendiksen, Kjell H.; Langsholt, Morten; Liu, Lan
Highlights: The effect of viscosity on slug bubble velocities has been quantified, based on a series of 241 experiments, in order to improve predictive models of slug flow in the laminar region. The dependency of individual slug bubble velocities on slug lengths and bubble nose shape and position has been investigated in detail for selected experiments. A new slug bubble velocity model is presented, incorporating viscosity, which compares well with available high viscosity slug flow data. Abstract: The slug bubble velocity is one of the most important closure relations in multiphase flow models, and has been studied extensively for decades. Available models and correlations may provide quite reliable predictions for low viscosity liquids, but this is not always the case for high viscosities, mainly due to a lack of detailed data. An investigation of viscous slug flow was carried out, based on 241 experiments in a 15 m long horizontal pipe of 57 mm inner diameter, applying three different liquids with viscosities in the range of 240–730 cP. Measured parameters include slug bubble velocities, slug lengths, liquid holdup and pressure drop. A main objective has been to quantify the effect of viscosity on slug bubble velocities, in order to improve predictive models of slug flow in the laminar region. Slug front, tail and pattern velocities were obtained by cross-correlating holdup time series recorded at two locations at the end of the test section. The dependency of individual slug bubble velocities on slug lengths and bubble nose shape was investigated in detail for selected experiments. A new slug bubble velocity model has been developed, incorporating viscosity, which compares quite well with available high viscosity slug flow data.